Development of an in vitro compound screening system that replicate the in vivo spine phenotype of idiopathic ASD model mice - Maeda, Kazuma; Tanimura, Miki; Masago, Yusaku; Horiyama, Tsukasa; Takemoto, Hiroshi; Sasaki, Takuya; Koyama, Ryuta; Ikegaya, Yuji; Ogawa, Koichi (Frontiers in Pharmacology, 2024)
Autism Spectrum Disorder (ASD) is a developmental condition characterized by core symptoms including social difficulties, repetitive behaviors, and sensory abnormalities. Aberrant morphology of dendritic spines within the cortex has been documented in genetic disorders associated with ASD and ASD-like traits. We hypothesized that compounds that ameliorate abnormalities in spine dynamics might have the potential to ameliorate core symptoms of ASD. Because the morphology of the spine is influenced by signal inputs from other neurons and various molecular interactions, conventional single-molecule targeted drug discovery methods may not suffice in identifying compounds capable of ameliorating spine morphology abnormalities.In this study, we focused on spine phenotypes in the cortex using BTBR T + Itpr3 tf /J (BTBR) mice, which have been used as a model for idiopathic ASD in various studies. We established an in vitro compound screening system using primary cultured neurons from BTBR mice to faithfully represent the spine phenotype.The compound library mainly comprised substances with known target molecules and established safety profiles, including those approved or validated through human safety studies. Following screening of this specialized library containing 181 compounds, we identified 15 confirmed hit compounds. The molecular targets of these hit compounds were largely focused on the5-hydroxytryptamine receptor (5-HTR).Furthermore, both 5-HT1AR agonist and 5-HT3R antagonist were common functional profiles in hit compounds. Vortioxetine, possessing dual attributes as a 5-HT1AR agonist and 5-HT3R antagonist, was administered to BTBR mice once daily for a period of 7 days. This intervention not only ameliorated their spine phenotype but also alleviated their social behavior abnormality. These results of vortioxetine supports the usefulness of a spine phenotype-based assay system as a potent drug discovery platform targeting ASD core symptoms.